A pre-PEXEL histidine-rich protein II erythrocyte binding peptide as a new way for anti-malarial vaccine development (2007)
The Plasmodium falciparum malaria parasite produces several proteins characterised by an unusually high histidine content in infected red blood cells (iRBC). The histidine-rich protein II (HRP-II) is synthesised throughout the parasite’s asexual and gametocyte stages, transported through the parasitophorous vacuole (PV) to iRBC cytosol and membrane and released to the bloodstream via a PEXEL motif. Immunogenicity and protection-inducing studies were begun with an RBC high activity binding peptide (HABP) from this protein named 6800 (preceding the PEXEL motif) in the experimental Aotus monkey model. Modifying critical residues (determined by glycine scanning in this HABP) induced immunogenicity and protection against experimental challenge. Native 6800 did not bind to any HLA-DR?1? molecule, but these modified HABPs acquired the ability to specifically bind to HLA-DR?1?0701. 1H NMR studies revealed that whilst 6800 had a random structure, modified immunogenic and protection-inducing 24230 displayed very short ?-helical segments allowing appropriate binding to the MHCII-pep-TCR complex. Modifications in conserved HABPs preceding PEXEL motifs thus open up new avenues for subunit-based, multi-component synthetic anti-malarial vaccine development.